P143 Memories matter: Facilitating expression though creativity. (1st October 2013) - Ho, Debbie; Davies, Andrea; Bailey, Val; Carr, Susie; Maxwell, Sarah; Rendell, Charlie
Abstract : Introduction: In 2012 the Hospice extended the reach of its traditional family support services with two dedicated events for children and families. Each event was designed to facilitate remembrance, and promote self care and confidence within families whose lives had been inextricably changed though loss. Aim: To create a bespoke event for children and adults (both) independently and collectively through providing a range of creative and therapeutic activities. To test simple strategies for engagement and interaction, and evaluate the quality of the experience through simple discovery techniques. To reduce the sense of isolation experienced by children following the loss of someone loved by them. Method: 28 children in total attended the events which took place in July and November 2012. Led by the family support and bereavement care service, and supported by the art therapist and trained volunteers, children and families who had previously engaged in pre-bereavement support, or post bereavement 1:1 or small group support were invited to the events. A range of activities were developed in consultation with the art therapist with a view to engaging children across a broad range of ages. Some sought to unify children and adult involvement. Activities included: Making memory felts Making a web of support using a ball of wool to create a shared bond Making an interactive advent calendar which featured on the Hospice website throughout December creating a meaningful focus as families faced a first Christmas. Results: Children and families unanimously placed a high value on the quality of the event in terms of: Therapeutic value Facilitating dialogue which acknowledged the loss of the person who had died Making meaningful memories Reducing the sense of isolation within families Staff and volunteer experience was enriched through their involvement.